2015
DOI: 10.3233/nua-140042
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal involvement in glucose facilitation of recognition memory: Event-related potential components in a dual-task paradigm

Abstract: Con and Riby, Leigh (2015) Hippocampal involvement in glucose facilitation of recognition memory: Event-related potential components in a dual-task paradigm. Nutrition and Aging, 3 (1 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Six studies were conducted with healthy adult participants (An, Jung, Kim, Lee, & Kim, 2015;Brown & Riby, 2013;Parent et al, 2011;Riby et al, 2008;Serra-Grabulosa, Adan, Falcon, & Bargallo, 2010;Zanchi et al, 2018). Three studies were conducted with healthy elderly samples (Gagnon et al, 2012;Knott, Messier, Mahoney, & Gagnon, 2001;Scholey et al, 2015). One study was conducted with healthy adolescent participants (Smith et al, 2009) and one study was conducted with adults diagnosed with chronic schizophrenia (Stone, Thermenos, Tarbox, Poldrack, & Seidman, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies were conducted with healthy adult participants (An, Jung, Kim, Lee, & Kim, 2015;Brown & Riby, 2013;Parent et al, 2011;Riby et al, 2008;Serra-Grabulosa, Adan, Falcon, & Bargallo, 2010;Zanchi et al, 2018). Three studies were conducted with healthy elderly samples (Gagnon et al, 2012;Knott, Messier, Mahoney, & Gagnon, 2001;Scholey et al, 2015). One study was conducted with healthy adolescent participants (Smith et al, 2009) and one study was conducted with adults diagnosed with chronic schizophrenia (Stone, Thermenos, Tarbox, Poldrack, & Seidman, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the included studies used Electroencephalography (EEG) as a measure of brain activity, five of these focused on event-related potentials (ERPs: Brown & Riby, 2013;Knott et al, 2001;Riby et al, 2008;Smith et al, 2009;Scholey et al, 2015). Two studies reported spectral analysis of resting EEG (An et al, 2015;Knott et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While cognitive domains implicated in the glucose facilitation effect have been argued to preferentially enhance hippocampusdependent tasks, relatively limited research has directly explored underlying neurophysiological mechanisms in the human brain. Several event-related potential (ERP) studies support the involvement of the hippocampus (Smith et al, 2009;Brown and Riby, 2013;Scholey et al, 2015). Further evidence for the involvement of the hippocampus in the effect stems from a study using fMRI (Parent et al, 2011).…”
Section: Introductionmentioning
confidence: 99%